Autophagy - A Double-Edged Sword Cell Survival or Death? - Bailly, Yannick (IntechOpen, 2013)
The chapters in this book review the latest advances in the molecular mechanisms of autophagy, highlighting some of the most challenging research topics. The focus is mainly on how this basic cell defense mechanism comes into play in various pathologies, including liver diseases, myopathies, infectious diseases, cancers and neurodegenerative diseases. In these diseases, the contradictory autophagy roles of cell survival versus cell death emphasize the necessity of taking into account this double-edged nature in future development of already promising, autophagy- modulating, therapies.